How to choose initial treatment in multiple sclerosis patients: a case-based approach - Apóstolos, Samira Luisa Pereira; Boaventura, Mateus; Mendes, Natalia Trombini; Teixeira, Larissa Silva; Campana, Igor Gusmão (Arquivos de Neuro-Psiquiatria, 2022)
Background: Immunotherapy dramatically changed the natural history of multiple sclerosis (MS), which was classically associated with severe disability. Treatment strategies advocate that early control of disease activity is crucial to avoid progressive disability, and the use of high efficacy drugs may be beneficial, but safety is a concern. Choosing the disease-modifying therapy is challenging in clinical practice and should be further discussed. Objective: To discuss the state of art of selecting the initial therapy for relapsing MS patients. Methods: We used a case-based approach followed by clinical discussion, exploring therapeutic options in different MS settings. Results: We presented clinical cases profile compatible with the use of MS therapies, classified into moderate and high efficacy. In the moderate efficacy group, we discussed interferons, glatiramer acetate, teriflunomide and dimethyl fumarate, while in the high efficacy group we discussed fingolimod, cladribine, natalizumab, ocrelizumab, alemtuzumab and ofatumumab. Conclusion:  Advances in MS treatment are remarkable. Strong evidence supports the use of early high efficacy therapy. However, biomarkers, clinical and radiologic prognostic factors, as well as patients' individual issues, should be valued and considered for a personalized treatment decision.
Keywords: Multiple Sclerosis; Therapeutics